Transforming the volunteer experience in the social service sector - SIDHU, Dalvin (Institutional Knowledge at Singapore Management University, 2023)
Transforming the Volunteer Experience in the Social Service Sector is the first analysis report of its kind that focuses on investigating and enhancing volunteerism in Singapore. Through the perspectives of volunteers and volunteer managers via surveys and in-depth interviews, this report reveals a framework depicting five key features that contribute towards a quality volunteering experience. The study also makes recommendations on the actionable steps and strategies that Social Service Agencies can adopt to engage their volunteers more strategically, so that they can play a more significant role in delivering enhanced quality services to service users.